Effects of Potassium Ion Substitution on Lattice Parameters and Proton Migration in Barium Phosphate - Jeong, Yong-Chan; Kim, Byung-Kook; Kim, Yeong-Cheol (IOP PUBLISHING LTD, 2013)
The effects of substituting a potassium ion for a barium ion in barium phosphate on lattice parameters and proton migration were investigated using density functional theory. A proton inserted into the material preferred to be attached to an oxygen ion near the potassium ion to compensate for the positive charge of the potassium ion that is less than that of the barium ion. Lattice parameters were investigated as a function of the potassium ion concentration. The lattice parameter a increased linearly with the potassium ion concentration, while the lattice parameter c remained almost constant. These trends were in good agreement with the experimental results. When the proton migrated from the ab-plane containing the potassium ion to the plane free of the potassium ion, a high energy barrier of 0.58 eV was required for proton migration. This value was also in good agreement with the experimentally measured energy barriers (0.53-0.58 eV). (C) 2013 The Japan Society of Applied Physics
Keywords: INITIO MOLECULAR-DYNAMICS; TOTAL-ENERGY CALCULATIONS; CONDUCTIVITY; CONDUCTORS; ZIRCONATE; CRYSTAL; SC